Is Awareness on Plastic Pollution Being Raised in Schools? Understanding Perceptions of Primary and Secondary School Educators - Dalu, Mwazvita T. B.; Cuthbert, Ross N.; Muhali, Hulisani; Chari, Lenin D.; Manyani, Amanda; Masunungure, Current; Dalu, Tatenda (Sustainability, 2020)
Plastic pollution is a major global issue and its impacts on ecosystems and socioeconomic sectors lack comprehensive understanding. The integration of plastics issues into the educational system of both primary and secondary schools has often been overlooked, especially in Africa, presenting a major challenge to environmental awareness. Owing to the importance of early age awareness, this study aims to investigate whether plastic pollution issues are being integrated into South African primary and secondary education school curriculums. Using face-to-face interviews with senior educators, we address this research problem by investigating (i) the extent to which teachers cover components of plastic pollution, and (ii) educator understandings of plastic pollution within terrestrial and aquatic environments. The results indicate that plastic pollution has been integrated into the school curriculum in technology, natural science, geography, life science, life skills and life orientation subjects. However, there was a lack of integration of management practices for plastics littering, especially in secondary schools, and understanding of dangers among different habitat types. This highlights the need for better educational awareness on the plastic pollution problem at both primary and secondary school level, with increased environmental programs needed to educate schools on management practices and impacts.